Acquired transdiaphragmatic hernia: an unusual cause of cardiac tamponade. (March 2017) - D'Orio, Virginie; Demondion, Pierre; Lebreton, Guillaume; Coutance, Guillaume; Varnous, Sheida; Leprince, Pascal
Transdiaphragmatic peritoneopericardial hernia is a rare complication after peritoneopericardial window formation, coronary artery bypass grafting using the gastroepiploic artery, or subxiphoid epicardial pacemaker insertion. We describe two different clinical presentations of transdiaphragmatic peritoneopericardial hernia in patients who had undergone recent heart transplantation. One was an exceptional case of cardiac tamponade caused by small bowel strangulation through a diaphragmatic defect.